Montenegro : Request for Purchase under the Rapid Financing Instrument; Press Release; Staff Report; and Statement by the Executive Director for Montenegro. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2020)
The COVID-19 pandemic will hit Montenegro hard, as tourism is a key industry. Fiscal space has eroded in recent years due to large public capital outlays, and the COVID-19 crisis is creating new budgetary strains as health spending and other expenditures rise, while the economic contraction lowers revenues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet